When confessing sin feels good: The practice of confession explored through the lens of Hartmut Rosa's theory of resonance - Graff-Kallevåg, Kristin (Dialog, 2023)
This paper draws on a qualitative study of how young people engaged in two youth ministries in the Church of Norway reflect on sin and shame in relation to their existential dilemmas . The authors analyze this practice through the lens of Hartmut Rosa's concept of resonance, arguing that there is consonance between how young people in the study express shame and the Lutheran understanding of sin as being curved in on oneself. Both sin and shame prevent the subject from being open to the world, thus constituting resistance to resonance. Yet, the practice of confessing sin may be a remedy to this closing in on oneself, as confession affords a resonant space, countering feelings of existential inadequacy caused by both sin and shame. Bringing the concept of vulnerability into the discussion, the paper further argues that confessing sin may prove healing and liberating also for experiences of shame as long as it does not violate the subject's ability to speak with her own voice or involve harmful god-images or harmful power dynamics.